Analysis of the Application of Rhetorical Style in the Interview Process of Passport Making - Wahyuddin, Muh. Asri; Mujahid, Mujahid; Sukmarini, Andi Vita (Journal of Management and Administration Provision, 2024)
This study aims to: (1) analyze the application of rhetorical styles by immigration officers in the passport interview process at the Makassar Class 1 TPI Immigration Office and its impact on the interaction between officers and passport applicants, and (2) identify the obstacles faced by interview officers in applying these rhetorical styles. Using a qualitative descriptive approach and case study, data were collected through interviews, observations, and document analysis. The research location was at the Makassar Class 1 TPI Immigration Office, lasting for two months. Primary data were obtained from interviews and observations, while secondary data came from official documents and related literature. Data analysis techniques include reduction, organization, presentation, interpretation, and drawing conclusions, with validity tested using triangulation of sources, time, and methods. The results of the study indicate that immigration officers use various rhetorical styles, such as persuasive, assertive, straightforward, and authoritative, to explain the passport application procedure, convince applicants, and ensure compliance, with elements of ethos, pathos, and logos appearing in the interaction. The application of effective rhetorical styles has a positive impact on the interaction between officers and applicants, increasing compliance and the efficiency of the interview process. The challenges faced by officers include adjusting rhetorical style to the diverse preferences of applicants, dealing with applicants with different backgrounds, maintaining a balance between clarity of information and friendliness, and time constraints when the number of applicants is large.